Spectroscopic studies of Organosolv Lignin from Arecanut Husk - Kulkarni, H.G.; Sirmokadam, N.N.; Shenvi, A.K.; Hegde, G.M. (Asian Journal of Chemistry, 2010)
The organosolv (ethanol) lignin of arecanut husk was isolated in 1 N concentrated HCl and studied by UV-visible and IR spectroscopic studies. The lignin showed maximum absorption in the range of 280–285 nm. The values of extinction coefficient were calculated.